DIGITAL HUMAN MODELING IN ERGONOMIC RISK ASSESSMENT OF WORKING POSTURES FOR HORIZONTAL LOG BAND SAWMILL - Cong Chi, Tran; Thi Tham, Nguyen; Ba Vu, Nguyen; Thi Ha, Dang (Journal of Forestry Science and Technology, 2020)
Digital Human Models (DHMs) are becoming a useful tool for ergonomics design and worker operations analysis in the industry field. The present study aims to initially assess the risk of biomechanical and the postures assumed by a worker during the manual operation of the horizontal log band sawmill (HLBS) machine in Vietnam. The Rapid Upper Limb Assessment (RULA) and Biomechanical compression force (BMCF) methods of Ergonomic Design & Analysis module in CATIA software were used to analyze pushing and pulling operation postures on the HLBS machine. The results indicate that the RULA score of pulling and pushing operation of the 5th percentile workers is 5. For the 95th percentile, the analysis scores are 7 and 6, respectively. The biomechanical analysis results show that the compression force of 5th and 95th percentile workers in pushing operation are1433 and 1718 N, while pulling operations are 1379 N and 1654, respectively. The results indicate that the risk levels associated with two operation postures are high. Therefore, it is necessary to implement ergonomic interventions to reduce risk levels of these operations. This study results also show that Ergonomic Design & Analysis module in CATIA software is very useful to study ergonomics in workstations and industrial environments.